2012
DOI: 10.1007/s00415-012-6439-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, pathological, and genetic mutation analysis of sporadic inclusion body myositis in Japanese people

Abstract: Previous studies have identified several genetic loci associated with development of familial inclusion body myopathy. However, there have been few genetic analyses of sporadic inclusion body myositis (sIBM). In order to explore the molecular basis of sIBM and to investigate genotype-phenotype correlations, we performed a clinicopathological analysis of 21 sIBM patients and screened for mutations in the However, we advocate further clinicopathology and investigation of additional candidate genes in a larger co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 29 publications
(49 reference statements)
1
28
0
Order By: Relevance
“…The so-called "rimmed vacuoles" are considered the hallmark for sIBM; nevertheless, they are seen in many other muscle disorders, for example in inclusion body myopathy with Paget's disease and frontotemporal dementia (IBMPFD), in oculopharyngeal muscular dystrophy, or in myofibrillar myopathies [1]. Additionally, tubulofilamentous inclusions in the cytoplasm or in the nuclei can be found on electron microscopy in a variety of neuromuscular diseases [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…The so-called "rimmed vacuoles" are considered the hallmark for sIBM; nevertheless, they are seen in many other muscle disorders, for example in inclusion body myopathy with Paget's disease and frontotemporal dementia (IBMPFD), in oculopharyngeal muscular dystrophy, or in myofibrillar myopathies [1]. Additionally, tubulofilamentous inclusions in the cytoplasm or in the nuclei can be found on electron microscopy in a variety of neuromuscular diseases [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study [32], reported that the p.V805A variant in MYH2 (gene associated with hIBM3) significantly increased the risk of developing sIBM (RR = 12.2). However, none of the patients with that variant reported joint contractures or external ophthalmoplegia, a family history of IBM or consanguineous marriage [32]. This was the first report of a MYH2 gene mutation described in non-familial cases.…”
Section: Muscle Disorders Similar To Sibmmentioning
confidence: 99%
“…Immunohistochemical studies of myosin heavy chain isoforms showed atrophy or loss of muscle fibres expressing myosin heavy chain IIa or IIx, which may provide important clues for establishing the pathogenicity of this variant. In the same study, a novel missense mutation c.1719G > A (p.V566M) in the LIM domain binding 3 gene ( LDB3 , also known as ZASP ; causative gene for zaspopathy, a subtype of myofibrillar myopathies), coding for Z-band alternatively spliced PDZ-motif-containing protein, was reported in one of the patients [32]. This finding indicates LDB3 mutations might cause abnormalities in the Z-band in skeletal muscle resulting in the disease observed in this patient.…”
Section: Muscle Disorders Similar To Sibmmentioning
confidence: 99%
“…_While this can usually be done on the basis of the clinical and pathological phenotype, the distinction can be difficult in some cases of hIBM when there is an inflammatory infiltrate in the muscle biopsy. A recent Japanese study which screened for mutations in known hIBM and myofibrillar myopathy genes in a group of 21 patients with a diagnosis of inclusion body myositis did not find any mutations in VCP or GNE, but three patients had a mutation in MYHC2A which causes hIBM-3 (Cai et al, 2012). In another study of 79 IBM patients, pathogenic mutations in VCP were found in two patients who met the diagnostic criteria for IBM (Weihl et al, 2015).…”
Section: Brief Overview Of Pathogenesis and Genetic Susceptibility Famentioning
confidence: 98%